2022
DOI: 10.3390/universe8040233
|View full text |Cite
|
Sign up to set email alerts
|

Post-AGB Stars as Tracers of AGB Nucleosynthesis: An Update

Abstract: The chemical evolution of galaxies is governed by the chemical yields from stars, and here we focus on the important contributions from asymptotic giant branch (AGB) stars. AGB nucleosynthesis is, however, still riddled with complexities. Observations from post-asymptotic giant branch (post-AGB) stars serve as exquisite tools to quantify and understand AGB nucleosynthesis. In this contribution, we review the invaluable constraints provided by post-AGB stars with which to study AGB nucleosynthesis, especially t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 70 publications
2
13
0
Order By: Relevance
“…This is consistent with the dominant sprocess origin from low-and intermediate-mass stars, where the 13 C neutron source is not dependent on metallicity, but the neutron to heavy seed ratio declines with metallicity. Image reproduced with permissions from Kamath and Van Winckel (2022), copyright by the authors from about 1120 down to 0.5 (Hansen et al 2018), and indicating the different decline of the abundance curve as a function of A. Some of the r-process enriched stars show an "actinide boost", i.e.…”
Section: Galactic Chemical Evolution (Gce)mentioning
confidence: 99%
“…This is consistent with the dominant sprocess origin from low-and intermediate-mass stars, where the 13 C neutron source is not dependent on metallicity, but the neutron to heavy seed ratio declines with metallicity. Image reproduced with permissions from Kamath and Van Winckel (2022), copyright by the authors from about 1120 down to 0.5 (Hansen et al 2018), and indicating the different decline of the abundance curve as a function of A. Some of the r-process enriched stars show an "actinide boost", i.e.…”
Section: Galactic Chemical Evolution (Gce)mentioning
confidence: 99%
“…This dispersion, on the other hand, is necessary to account for the s-element abundance patterns observed in individual C-stars. We note, nevertheless, that the correlation [hs/ls] vs. [Fe/H] is not clearly observed in post-AGB stars, the progeny of AGB stars, at least in the metallicity range studied [37]. This shows the complexity of the s-process nucleosynthesis in AGB stars.…”
Section: S-elementsmentioning
confidence: 61%
“…In any case, this question remains unsolved. Note that most of post-AGB stars show also C/O ratios very close to 1 [38], which is not either understandable on theoretical grounds.…”
Section: The Observational Frameworkmentioning
confidence: 83%
“…Observational studies of post-AGB stars in the Galaxy (e.g. Van Winckel & Reyniers 2000;Rao et al 2012;De Smedt et al 2015;Kamath et al 2022) and the Magellanic Clouds (MCs) (e.g. Kamath et al 2014Kamath et al , 2015 have shown that they are far more chemically diverse than anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study by Kamath et al (2017) reported a subset of luminous single post-AGB stars (one in the Small Magellanic Cloud (SMC) and two in the Galaxy) that exhibited neither traces of carbon enhancements nor s-process elements, suggesting a likely failure of the third dredge-up (TDU). Further expanding on this, a recent investigation by Kamath et al (2022) categorised single post-AGB stars with similar atmospheric parameters into two groups: those displaying s-process enrichment and those exhibiting no s-process enrichment.…”
Section: Introductionmentioning
confidence: 99%